IMPLEMENTATION OF CRM METHODS TO IMPROVE SALES QUALITY OF BUNUT SEBRANG UMI CLOTHING SHOP - Windi Safitri; Guntur Maha Putra; Febby Madonna Yuma (Jurnal Riset Informatika, 2022)
Along with the times, the business world is currently experiencing rapid development, especially in the business world, such as selling fashion products. Therefore, a good strategy is needed. In maintaining more advanced competitiveness, companies must develop information technology. Another thing that must be considered in making the business progress is maintaining customer relations, managing good relationships with new customers, or regular customers using the Customer Relationship Management (CRM) method. The application of the CRM method will make it easier for Umi Clothing Store owners to retain existing customers and make it easier for store owners to get new customers. The research method used in this research is qualitative research. This research will only utilize data obtained from the research location and input it without changing anything.